The Effect of Public Policy Transparency on Citizen Trust in Government Institutions - Izunna Ogudu Chukwu (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
Public policy transparency is a fundamental principle of democratic governance, fostering accountability, reducing corruption, and enhancing citizen trust in government institutions. This paper examines the relationship between transparency in public policy and citizen trust, analyzing theoretical frameworks, empirical evidence, and case studies from different countries. It explores how transparency mechanisms—such as open data initiatives, freedom of information laws, and participatory governance—affect public perceptions of government credibility. The study also discusses challenges to achieving transparency, including bureaucratic resistance, information overload, and political manipulation. Ultimately, the findings suggest that while transparency is a critical factor in building trust, its effectiveness depends on implementation quality, citizen engagement, and institutional responsiveness.